2003
DOI: 10.1177/106342660301100103
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Developing and Implementing Effective Policy in Children's Mental Health

Abstract: This article presents a framework to be used in studying public policy development and implementation in children's mental health. It particularly focuses on policy related to the establishment of community-based systems of care.The framework is based on a review of the literature on policy development and implementation. It focuses on four dimensions: the stages of policy development and implementation, the relationships among different levels of government, the relationships among different service sectors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…Following the changes, GPs have continued their involvement in the 6–8 week review but provision of other standard reviews has essentially ceased. This finding is broadly in line with what would have been expected from the policy recommendations, although it is worth noting that policy is by no means always implemented as intended [16,17]. Our findings also show that, since 2005, GPs have had minimal involvement in provision of the selective 24 month review.…”
Section: Discussionsupporting
confidence: 87%
“…Following the changes, GPs have continued their involvement in the 6–8 week review but provision of other standard reviews has essentially ceased. This finding is broadly in line with what would have been expected from the policy recommendations, although it is worth noting that policy is by no means always implemented as intended [16,17]. Our findings also show that, since 2005, GPs have had minimal involvement in provision of the selective 24 month review.…”
Section: Discussionsupporting
confidence: 87%
“…Alternatively, policies that target individual outlets may have a more limited effect than area-wide or city-wide policies. Policy design variables such as these can be important determinants of whether or not policies will achieve their intended purpose (Friedman, 2003;McLaughlin, 1987;Paul & Sabatier, 1986). However, researchers have examined why public policies fail to meet their goals following adoption, and many have concluded that some policies fail, not because they take the wrong approach, but because they are not well-implemented (Bardach, 1974;Elmore, 1979;Pressman & Wildavvsky, 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Ambiguity, limited resources, and resistance to change may inhibit full implementation of the principles set forth in the NFC report. From an historical perspective, Friedman (2003) observes, "the mere articulation of policy through legislation or regulation is rarely adequate to accomplish the goals of the policy" (p. 11). Therefore, the question remains: How can we implement the recommendations from the NFC initiative in a strategic and passionate way to prevent it from becoming another relatively unused report?…”
Section: "Achieving the Promise" Through School Mental Healthmentioning
confidence: 98%